PAX7 gene polymorphism in muscular temporomandibular disorders as potentially related to muscle stem cells - Valquiria Quinelato (BMC, 2021)
Abstract Background Temporomandibular disorders (TMD) are a group of painful and debilitating disorders, involving the masticatory muscles and/or the temporomandibular joint (TMJ). Chronic TMD pain can be associated with genetic changes in the key muscle development genes. Objective To evaluate the association between polymorphisms in the PAX7 (paired box 7) gene and masticatory myalgia in patients with temporomandibular disorders (TMD). Materials and methods This is a case-control study. Patients with TMD were divided into two groups: (a) presence of muscular TMD (n = 122) and (b) absence of muscular TMD (n = 49). Genomic DNA was obtained from saliva samples from all participants to allow for genotyping single nucleotide polymorphisms in PAX7 (rs766325 and rs6659735). Over-representation of alleles was tested using chi-square or Fisher’s exact tests. Values of p < 0.05 were considered to be statistically significant. Results Individuals without muscular TMD were less likely to have the PAX7 rs6659735 GG genotype (p = 0.03). No associations were found for PAX7 rs766325. Conclusions Alterations in PAX7 may influence muscular pathophysiology and individuals with TMD and the rs6659735 homozygous genotype (GG) are seemingly associated with muscular involvement of the disorder. No associations were found in the region rs766325.